2021
DOI: 10.1186/s12920-021-01139-y
|View full text |Cite
|
Sign up to set email alerts
|

Mutational and clinical spectrum of Japanese patients with hereditary hemorrhagic telangiectasia

Abstract: Background Hereditary hemorrhagic telangiectasia (HHT) is a dominantly inherited vascular disorder characterized by recurrent epistaxis, skin/mucocutaneous telangiectasia, and organ/visceral arteriovenous malformations (AVM). HHT is mostly caused by mutations either in the ENG or ACVRL1 genes, and there are regional differences in the breakdown of causative genes. The clinical presentation is also variable between populations suggesting the influence of environmental or genetic backgrounds. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
2
9
1
Order By: Relevance
“…Comparing our results with patients with HHT with PVs in ENG (HHT1) and ACVRL1 (HHT2), our patients presented with the same spectrum of HHT features as seen in other populations with HHT. The frequency of PAVMs (approximately 40%) is comparable with what have been reported in patients with HHT1, approximately 50%–75% 20–24. In patients with HHT2, the frequency of PAVMs is generally reported to be lower than in HHT1, 5%–15% 20 21 24.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Comparing our results with patients with HHT with PVs in ENG (HHT1) and ACVRL1 (HHT2), our patients presented with the same spectrum of HHT features as seen in other populations with HHT. The frequency of PAVMs (approximately 40%) is comparable with what have been reported in patients with HHT1, approximately 50%–75% 20–24. In patients with HHT2, the frequency of PAVMs is generally reported to be lower than in HHT1, 5%–15% 20 21 24.…”
Section: Discussionsupporting
confidence: 79%
“…The frequency of epistaxis is in general lower than in other studies, for example, Torring et al 21 and Kitayama et al, 20 who reported the proportion of epistaxis to be over 90% in both HHT1 and HHT2 20 25. Only one patient in our population experienced severe epistaxis, and furthermore, the mean age of first episode is 18 years of age (table 2), which is older than that of HHT1 and HHT2.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Mutations in this region are associated with HHT2, an increased incidence of pulmonary arterial hypertension [87][88][89] , and with other ALK family-associated diseases such as brachydactyly type A2 (ALK6) 90,91 and Loeys-Dietz syndrome (ALK5) 92,93 . ACVRL1 p.Arg484Gln has also been identified in HHT2 94 and in childhood-onset pulmonary arterial hypertension 95 . p.Arg484Gln.…”
Section: Variants In Acvrl1 and Other Mutation-intolerant Mendelian V...mentioning
confidence: 99%
“…GDF2 heterozygous variants were initially described as causing an HHT-like syndrome [ 36 ] and, more recently, in a family meeting full Curaçao Criteria clinical designation [ 37 ]. Genetic testing for ACVRL1 , ENG , SMAD4, and GDF2 is widely performed as part of HHT diagnostics [ 21 , 22 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Genotyped patients and families are commonly referred to as HHT type 1 ( ENG , OMIM #187300), HHT type 2 ( ACVRL1 , OMIM #600376), JPHT ( SMAD4 , (OMIM ##175050), and HHT type 5 ( GDF2 , OMIM # 615506).…”
Section: Introductionmentioning
confidence: 99%